1993
DOI: 10.1159/000196231
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Sleep Apnea among Japanese Industrial Workers Determined by a Portable Sleep Monitoring System

Abstract: We developed a new portable sleep monitoring system and studied the prevalence of sleep apnea syndrome among Japanese industrial workers. This device assessed three kinds of parameters: nasal airflow, tracheal sound and electrocardiogram (ECG), and digitally stored the clock time of the onset of apnea, apnea duration and R-R intervals by a built-in microcomputer. After monitoring, the portable sleep monitor was connected to a host computer, and apneic episodes, the so-called ‘apnea index’ as apneic episodes co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(10 citation statements)
references
References 5 publications
0
10
0
Order By: Relevance
“…The magnitude of this association is similar to that reported in the SHHS, demonstrating that 46% of participants with an RDI of 15 or greater had sleepiness symptoms using the same definition of sleepiness used in the current analysis (ESS score > 10). 34 Although the specificity and sensitivity of daytime sleepiness may be less in older people with many comorbidities, the evidence for significantly greater odds of daytime sleepiness with SDB underscores the importance of assessing this symptom in relationship to SDB in older people.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The magnitude of this association is similar to that reported in the SHHS, demonstrating that 46% of participants with an RDI of 15 or greater had sleepiness symptoms using the same definition of sleepiness used in the current analysis (ESS score > 10). 34 Although the specificity and sensitivity of daytime sleepiness may be less in older people with many comorbidities, the evidence for significantly greater odds of daytime sleepiness with SDB underscores the importance of assessing this symptom in relationship to SDB in older people.…”
Section: Discussionmentioning
confidence: 99%
“…The magnitude of this association is similar to that reported in the SHHS, demonstrating that 46% of participants with an RDI of 15 or greater had sleepiness symptoms using the same definition of sleepiness used in the current analysis (ESS score > 10). 34 Although the specificity and sensitivity of daytime sleepiness may be less in older people with many comorbidities, the evidence for significantly greater odds of daytime sleepiness with SDB underscores the importance of assessing this symptom in relationship to SDB in older people.By examining the strength of the associations between risk factors and comorbidities according to definitions that differentiated central from obstructive events, these analyses provided further evidence that CAs and OAs were associated with a distinct constellation of risk factors and outcomes. In particular, an elevated CAI was associated with advancing age and with heart failure but not with indices of obesity.…”
mentioning
confidence: 99%
“…Finally, the prevalence of SDB could be lower in Japan. We doubt, however, that this is the case because previous studies, although not comprehensive in nature, demonstrated a similar prevalence of sleep apnea in the two countries 7–9 …”
Section: Discussionmentioning
confidence: 83%
“…We doubt, however, that this is the case because previous studies, although not comprehensive in nature, demonstrated a similar prevalence of sleep apnea in the two countries. [7][8][9] We speculate, therefore, that the proportion of undiagnosed SDB and the other sleep disorders must be greater in Japan than in the USA. Current data suggest that untreated OSAHS leads to sleepiness, 10 decreased quality of life, 11 automobile accidents, 12 systemic hypertension, 13 and cardiac disease.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence rate of sleep‐breathing disorders (SBD) in the Japanese population appears to be lower than that in Caucasians because marked obesity is rare in the Japanese 1–5 . However, it has been suggested that over 3% of the adult Japanese population suffer from an SBD, and it has been reported that the prevalence of the disease is comparatively high 6–8 . These reports suggest that if obesity is much less frequently seen in the Japanese compared with Caucasians, other contributing factors for developing an SBD must exist for the Japanese 9–15 …”
Section: Introductionmentioning
confidence: 99%